2021
DOI: 10.3390/molecules27010006
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Photocatalytic Performance of ZnO Nanoparticles Synthesized by Green Chemistry Using Different Botanical Extracts and Zinc Acetate as a Precursor

Abstract: In this work, the assessment of Azadirachta indica, Tagetes erecta, Chrysanthemum morifolium, and Lentinula edodes extracts as catalysts for the green synthesis of zinc oxide nanoparticles (ZnO NPs) was performed. The photocatalytic properties of ZnO NPs were investigated by the photodegradation of methylene blue (MB) dye under sunlight irradiation. UV-visible (UV-Vis) spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy, Transmission Electron Microscopy (TEM), X-ray Diffraction (XRD), Thermogravimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…2c). In general, the morphological study revealed the small particle size and high surface area of the nanoparticles, which matches the results obtained from XRD and most of the literature [30,31].…”
Section: Resultssupporting
confidence: 88%
“…2c). In general, the morphological study revealed the small particle size and high surface area of the nanoparticles, which matches the results obtained from XRD and most of the literature [30,31].…”
Section: Resultssupporting
confidence: 88%
“…ZnO has excellent chemical stability because of its hexagonal wurtzite structure at normal temperatures leading to a large Coulomb force for its positive and negative electron pairs [1]. ZnO is environmentally friendly, inexpensive, and abundant in nature and intrinsic defects such as oxygen vacancies or Zn interstitials are mostly on the surface of ZnO causing visible emissions [2,3]. All these unique properties make ZnO application in the ultraviolet (UV) and blue source and have efficient exciton emission [4].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the mean size of the nanospheres was estimated from the TEM image to be around 25 nm (Fig. 2 c) [ 35 , 36 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%